System estimate of breeding material of winter wheat for freezing tolerance - Г. В. Мазільніков; В. В. Сорокін; О. М. Кучеренко; В. А. Фоманюк (Plant Varieties Studying and Protection)
Proposed system approach for freezing tolerance estimate of breeding material of winter wheat allows to differentiate the samples by physiological properties of resistance to low temperatures and based on to carry out selecting parents for hybridization in changeable environments of global warming.